2016
DOI: 10.4049/jimmunol.1501889
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD147 and Calcium Exporter PMCA4 Uncouples IL-2 Expression from Early TCR Signaling

Abstract: The Ig superfamily member CD147 is upregulated following T cell activation and was shown to serve as a negative regulator of T cell proliferation. Thus, Abs targeting CD147 are being tested as new treatment strategies for cancer and autoimmune diseases. How CD147 mediates immunosuppression and whether association with other coreceptor complexes is needed have remained unknown. In the current study, we show that silencing of CD147 in human T cells increases IL-2 production without affecting the TCR proximal sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
(50 reference statements)
3
20
0
Order By: Relevance
“…As our previous study shown, CD147 is considered to be a HNSCC cell surface marker that could enhance the tumor initiation and progression . Studies also demonstrated that CD147 had negative role in regulating in T cell‐mediated immune responses and drugs targeting CD147 had anti‐angiogenesis and anti‐invasion activity . Our data determined that CD147 exerted positive effect on tumorigenicity and cancer progression of HNSCC both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…As our previous study shown, CD147 is considered to be a HNSCC cell surface marker that could enhance the tumor initiation and progression . Studies also demonstrated that CD147 had negative role in regulating in T cell‐mediated immune responses and drugs targeting CD147 had anti‐angiogenesis and anti‐invasion activity . Our data determined that CD147 exerted positive effect on tumorigenicity and cancer progression of HNSCC both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 61%
“…5 Studies also demonstrated that CD147 had negative role in regulating in T cell-mediated immune responses and drugs targeting CD147 had anti-angiogenesis and anti-invasion activity. [25][26][27][28] Our data determined that CD147 exerted positive effect on tumorigenicity and cancer progression of HNSCC both in vitro and in vivo. In addition, CD147 expression level is positively correlated with clinical outcome and tumor histological grade in HNSCC.…”
Section: Discussionmentioning
confidence: 63%
“…Further, two studies have reported reduced phosphorylation of early TCR signaling components and reduced calcium mobilization upon CD147 silencing (34) or CD147 Ab treatment (7), whereas in another study enhanced JNK and p21-activated kinase 1 activation and thus higher NFAT transcriptional activity in CD147-silenced cells has been reported (48). We showed recently that interaction of CD147 with the plasma membrane calcium ATPase isoform 4 (PMCA4) bypasses TCR proximal signaling and inhibits IL-2 expression (64). Nevertheless, the understanding of the molecular functionality of CD147 is still incomplete.…”
mentioning
confidence: 90%
“…The lentiviral packaging plasmids psPAX and pMD2.G were from Addgene (Cambridge, MA); the pLKO.1-puro-nonmammalian short hairpin RNA (shRNA) control (shControl) was supplied by the German Science Center for Genome Research (Berlin, Germany). The pLKO.1-puro-CD147_333 (shCD147) containing an shRNA construct specific for human CD147 and the pBMN-IRES-GFP-HACD147etc containing the RNA interference (RNAi)resistant full-length CD147 with a hemagglutinin (HA)-tag (HACD147etc) were cloned as described previously (64).…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation